PESONA KARYA SASTRA DALAM PEMBELAJARAN BAHASA DAN BUDAYA INDONESIA - Woro Wuryani (STKIP Siliwangi, 2013)
Literary work is not born out of the void culture. Literary works can not be regarded as a mere fiction. Charge meanings into one literary charm. Learning literature always cause problems. Ranging from limited knowledge of the teacher to the position of literary works for students. The low ability of interpretation of a literary work of teachers and students is also a problem in the learning literature. Literary works to bring the mission to inculcate noble values and shape the character of his readers. Through literature teachers can shape the attitudes and character of students. Alienation literature for students is a problem that has occurred at this time. Literary works have a close relationship with culture. Literature was born from the culture of literature also reflects the culture. How many local wisdom drawn from the culture. One example of literary works are full of cultural values is rhyme. The values depicted in the poem describes that Indonesian culture is one of deliberation andconsensus.Keywords: literature, language learning, learning literature